Sports economics : theory, evidence and policy - Downward, Paul; Dawson, Alistair; Dejonghe, Trudo (London : Routledge, 2009)
This book provides a highly accessible introduction to the main theoretical, empirical and policy issues that emanate from the economic analysis of sport.
Chapter 1 : The Economics of Sport -- Chapter 2 :The Nature, Organization and Economic Significance of Sport -- Chapter 3 : The Economics of Sports Participation -- Chapter 4 : The Economics of Sports Participation: Evidence -- Chapter 5 : The Supply of Participant Sport: The Public and Private Sector -- Chapter 6 : The Supply of Participant Sport : Volunteers and Sports Clubs -- Chapter 7 : The Market for Professional Sports : General Themes -- Chapter 8 : Uncertainty of Outcome, Competitive Balance and Bias in Sports Leagues -- Chapter 9 : Cross-Subsidization in Professional Sports Leagues -- Chapter 10 : The Demand for Professional Team Sports : Attendance and Broadcasting -- Chapter 11 : The Labour Market in Professional Team Sports -- Chapter 12 : The Economics of Sports Events and Infrastructure
Includes bibliographical references and index.
Keywords: SPORTS -- ECONOMIC ASPECTS